Some issues regarding the calibration of the terrestrial laser scanner Leica Scanstation C10 - Antanavičiūtė, Urtė; Obuchovski, Romuald; Paršeliūnas, Eimuntas Kazimieras; Popovas, M. G. Darius; Šlikas, Dominykas (Geodesy and Cartography, 2013)
Some issues regarding the calibration results pertaining to the ground-based laser scanner Leica Scanstation C10 are presented and analysed. The calibration was carried out at Kyviškės Calibration Baseline (Jokela et al. 2002) and the special cyclic error detection baseline at the Research Institute of Geodesy of Vilnius Gediminas Technical University. The instrument was calibrated at 20, 100, 180, 200 and 260 m distances at Kyviškės Calibration Baseline and the indoors baseline from 1 to 15 m with continuous 1 m interval. The special procedure of indirect measurements was suggested to estimate errors of scanner measurements. During this procedure, the positions of the scanstation varied from the calibration baseline pillars to the standard tripods creating triangles of different shapes. The distances obtained by scanning targets placed on the calibration baseline pillars were compared with baseline standard distances. Suggested improvements in the calibration technology could be used for verification and calibration of terrestrial laser scanstations at the calibration baselines.